Coffee cherry processing waste to produce value-added products through clean production biorefineries - Yudiastuti, Silvia Oktavia Nur; Handayani, Wiwik; Sari, Elok Kurnia Novita; Wijaya, Rizza; Brilliantina, Aulia; Slamet, Ahmad Haris Hasanuddin (Indonesian Journal of Multidisciplinary Science, 2023)
Indonesia is the 4th largest coffee-producing country in the world. Coffee cherry can produce 60% CCPW, more than the core product of coffee beans as the main product produced. CCPW contains lignocellulosic material that can be converted into value-added products. This research optimizes the production of xylose and xylanase enzymes as an integrated process with a biorefinery model to increase the added value of CCPW using the Research Surface Methodology (RSM). Enzyme production is carried out using a bioprocess using Trichoderma viride. Xylose production is carried out using the dregs of xylanase production as raw material and xylanase enzymes which are produced in the integrated process. The xylanase and xylose produced are in the liquid phase. The treatment design for xylanase production is substrate concentration and incubation time, while for xylose production it is substrate concentration and xylanase concentration. Based on the optimization conducted, the optimum condition of xylanase production was 75% substrate concentration with an incubation time of 72 hours, which will result in xylanase an enzyme with an activity of 29.275 U/ml with desirability of 99.55%. On the other hand, the optimum condition of xylose production was 12.54% substrate concentration with a xylanase concentration of 4.01%, which will result in 0.53 g/L xylose content with desirability of 94.06%. These findings show that xylose production efficiency can be achieved through integrated two-stage biorefinery production for efficient and sustainable utilization of CCPW.